Practical time management : how to make the most of your most perishable resource - Haynes, Marion E. (Crisp Pub. Menlo ParkUS, 1991)
Presents principles and techniques which can assist the reader who has problems with time management, to become master of his time. Deals with subjects including: time management concepts; analysing time use; and, coping with common time wasters.